Antidiarrheal Effect of Lactobacillus fermentum Isolated from Dengke Naniura on Escherichia coli-induced Rats - Nasri, Nasri; Harahap, Urip; Silalahi, Jansen; Satria, Denny (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Diarrhea is discharge of abnormal and liquid stool with a frequency of 3-4 daily which caused by pathogenic organisms such as Escherichia coli, and other. Dengke Naniura is a traditional Batak Toba food that can produce probiotics (Lactobacillus fermentum). Probiotics are defined as live microorganisms that confer a health benefit on the host. Nutritional supplements combined between probiotics and prebiotics are called synbiotics, The purpose of this study was to analyze the preventive effect of diarrhea in rats given L.fermentum for 21 days. The preventive effect of diarrhea test begins with the giving of L.fermentum from day 1 to day 21. From day 7 to day 14 rats were induced with E.coli. Weight of the rats, stool consistency, onset of diarrhea, frequency of diarrhea, and duration of diarrhea were observed. The results of the observation that weight of rats in the L.fermentum group increased compared to group 1 (p<0.05). Consistency stool is soft (massless). Onset of diarrhea on day 1 after induced of E.coli in the group 1. Frequency of diarrhea increased to 9.25 Â± 0.50 times on day 14 (group 1). And diarrhea occurs for 10 days. Conclusion L.fermentum showed a preventive effect of diarrhea in rats induced E.coli.